Study of gene expression alteration in male androgenetic alopecia: evidence of predominant molecular signalling pathways. (1st November 2017) - Michel, L.; Reygagne, P.; Benech, P.; Jean‐Louis, F.; Scalvino, S.; Ly Ka So, S.; Hamidou, Z.; Bianovici, S.; Pouch, J.; Ducos, B.; Bonnet, M.; Bensussan, A.; et al.
Summary: Background: Male androgenetic alopecia (AGA) is the most common form of hair loss in men. It is characterized by a distinct pattern of progressive hair loss starting from the frontal area and the vertex of the scalp. Although several genetic risk loci have been identified, relevant genes for AGA remain to be defined. Objectives: To identify biomarkers associated with AGA. Methods: Molecular biomarkers associated with premature AGA were identified through gene expression analysis using cDNA generated from scalp vertex biopsies of hairless or bald men with premature AGA, and healthy volunteers. Results: This monocentric study reveals that genes encoding mast cell granule enzymes, inflammatory mediators and immunoglobulin‐associated immune mediators were significantly overexpressed in AGA. In contrast, underexpressed genes appear to be associated with the Wnt/β‐catenin and bone morphogenic protein/transforming growth factor‐β signalling pathways. Although involvement of these pathways in hair follicle regeneration is well described, functional interpretation of the transcriptomic data highlights different events that account for their inhibition. In particular, one of these events depends on the dysregulated expression of proopiomelanocortin, as confirmed by polymerase chain reaction and immunohistochemistry. In addition, lower expression of CYP27B1 in patients with AGA supports the notion that changes in vitamin D metabolism contributes to hair loss. Conclusions: This study provides compelling evidence for distinct molecular events contributing to alopecia that may pave the way for new therapeutic approaches.